Can German vocational training combat skill shortages in developing countries? Evidence from dual training system in the Philippines - Yamauchi, Futoshi; Kim, Taejong; Lee, Kye Woo; Tiongco, Marites (International Food Policy Research Institute, 2018)
This paper estimates the impacts of the Philippine Dual Training System (DTS) on labor market outcomes using a recent survey that tracked graduates from DTS and non-DTS programs provided by vocational training institutes. DTS programs partner with local employers to combine on-the-job training (OJT) with the conventional school- or center-based instruction, while non-DTS programs consist solely of the latter. The estimation results in Fuzzy Regression Discontinuity Design show a significantly positive impact on the most-recent monthly earnings. The impact significantly increases with the OJT intensity, measured by the number of hours of in-company OJT. The above results imply that the role played by OJT is essential to support higher earnings for DTS graduates.